Quality Characteristics of Fresh and Cooked Ground Beef can be Improved by the Incorporation of Lean Finely‐Textured Beef (LFTB). Issue 5 (23rd August 2016) - Moon, Courtney T.; Yancey, Janeal W. S.; Apple, Jason K.; Hollenbeck, Jace J.; Johnson, Timothy M.; Winters, Ashley R.
Abstract: Ground beef was formulated into six treatments of 82 or 93% lean with 0, 10, or 20% lean finely‐textured beef (LFTB). Batches ( n  = 5/treatment) were ground and formed into patties, then aerobically packaged for 5 days of simulated retail display to measure fresh color and lipid oxidation (TBARS). Additional patties were cooked to 71.1C before measuring external and internal cooked color, TBARS, and Lee‐Kramer shear force (LKSF). Lightness (L*), redness ( a *), and pH of fresh patties increased ( P  < 0.05), whereas TBARS values were decreased ( P  < 0.05) on days 1, 2, and 4 of display, with increasing LFTB percentage. Cooking loss was lowest ( P  < 0.05) in 20% LFTB patties, whereas LKSF declined ( P  < 0.05) with increasing LFTB inclusion. Thus, LFTB incorporation up to 20% improved the quality of fresh ground beef patties and tenderness of cooked patties, without detrimentally impacting ( P  > 0.07) cooked color. Practical Applications: Lean finely‐textured beef (LFTB) is a product made using an advanced meat recovery system from high‐fat, beef trimmings, and LFTB is treated with food‐grade ammonia to increase product pH and reduce potential pathogenic bacteria contamination. Even though LFTB has received considerable negative media coverage since 2012 (Yadavalli and Jones2014 ), results of this research indicate that the inclusion of LFTB up to 20% could lend many positive quality characteristics to both fresh and cooked ground beef patties. Decreased lipid oxidation along with improved fresh color could result in a product with greater quality attributes, especially a more appealing color to consumers. With no negative effects on cooked color or cooking loss and the potential for increased tenderness, LFTB inclusion is a viable way to produce a desirable product while ensuring more complete utilization of beef carcasses.